Analisis Pengendalian Kualitas dengan Menggunakan Metode Failure Mode and Effect Analysis dan Fault Tree Analysis pada Produk Songkok UD. XYZ - M. Danial Farrizqi; Deny Andesta (G-Tech: Jurnal Teknologi Terapan, 2024)
UD.XYZ is a songkok product manufacturing company headquartered in Gresik City. The company is still facing some shortcomings in its products. Therefore, companies must ensure stable product quality and reduce the risk of errors. When faced with a situation like this, quality control is very necessary to reduce the error rate and ensure that it does not exceed predetermined limits. In this research, FMEA and FTA methods were used. Implementing FMEA helps identify risks of error during the carpet manufacturing process. By using FMEA, defects that cause product failure can be identified and the risk of process failure assessed using the RPN value. The fault with the highest RPN will be analyzed in more detail using the FTA method to build a fault tree, from which the root of the problem can be identified. Based on the FTA results, improvement proposals are prepared in the hope of reducing the level of product defects. Research finds that there are three types of defects. The stitching is not neat (RPN=112), the embroidery is not good (RPN=100), and the size is not appropriate (RPN= 90).